Konsolidasi Tanah Kawasan Permukiman Kumuh Tepi Sungai Di Badur Bawah - Destia Farahdina; Dina Purnama (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2022)
Riverside settlement in the Lower Badur Bawah area, precisely along the deli river in Hamdan village, Medan Maimoon sub-district , are one of the slum settlements being unorganized and densely populatade and the disposal of household waste water is not in place which makes this area prone to slum. Therefore, it is necessary to revitalize the area with land consolidation method in order to create a healthy and comfortable encironmental area in accordance with the social, economic, and cultural conditions of the surrounding community but do not forget the regulations that apply in the city of Medan. This research was conducted by conducting interviews with stakeholders and field observations by observing the behavior and activities of the residents of Badur bawah to produce a physical desription of the exixting settlements. Based on the results of observations, it was found that the characteristics of residential residents showed the orientation of the building back to the river, the lack of sewerage and the lack of public space and open space areas. The solution to the existing problems through consolidation of regional land by providing decent housing in accordance with the needs and income of the population and utilizing the river border as a open space that can be used as an area of social activity between residents to strengthen a sense of togetherness so that a sense of protecting, maintaining security and evironmental comfort, especially the cleanliness of the Deli river.